Economic Fluctuations and Sectoral Growth in Iran: A Decade of Challenges and Opportunities (2010–2021) - G’olib Sultanmurodovich, Mustafoyev; Samariddin, Maxmudov; Farhod Fakhriddinovich, Ulugmurodov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This paper aims to analyze the export performance of Iran within the years 2010 to 2021 concerning Export Value Index, export earnings and the agricultural fishery and forestry growth rate. This work further highlights the cyclicality of the trading performance, which can be attributed to factors such as international sanctions, fluctuating oil prices and domestic policies. Though the export value has improved recently, the drastic export concentration to a single product means that Iran’s economy is exposed to volatility. There is again some stability in agriculture, but the agriculture industry is relatively still-developed and vulnerable to weather and economic cycles. The statistical analysis, including regression models, reveals the relationships between trade performance on one hand, and sectoral growth on the other. In line with its recommendations, this paper proposes a diversification of the economy, stabilisation of agriculture production, and establishment of trading relationships to stabilise economic growth.